Ain’t I a Woman? A Look at the Beauty of Blackness Amid the Internalized Body Politic of Genteel Whiteness - Miles-Tribble, Valerie (Religions, 2024)
Ain’t I a Woman? This question was raised by activist and self-emancipated former slavewoman Sojourner Truth, who validly questioned the body politic of identity when contextualized to perceptions of female personhood. Essentially, what Truth challenged were presumptions about the standards set to revere female bodies through markers of genteel Whiteness, while the worth of embodied Blackness, precisely the beauty of Black women, is reviled. In this article, I seek to raise awareness about factors of patriarchy and societal ramifications. Patriarchy is a systematized phenomenology of norms privileging the male gaze. The White male gaze, particularly in strongholds of power, influences the body politic of communal identity. Black women tend to lean on their faith to embody strength, yet patriarchy also encumbers the gendered body politic in religious spheres. As a womanist scholar, my analysis considers the intricate roles that patriarchy holds in the cultural production of a genteel, pretty woman image, wherein the aura of Whiteness grounds a body politic that deems Blackness as other. Despite the influences of prevailing macrosystems, I propose a theoethic of self-love to push against negatively biased identity boundaries by affirming ways to embrace Black beauty with a subversive imperative to love oneself regardless.